Improvement of the Quality of 3D Printing in the Mass Production of Parts - Rud V. D.; Zaika O. M.; Samchuk L. M.; Povstyana Y. S. (Журнал інженерних наук)
The article highlights the experience of using 3D printing at automotive enterprises manufacturing automotive wiring. The primary attention was paid to optimizing technologies and modernizing equipment in 3D printing in production conditions. This helped to improve the printing quality at the enterprise and reduce energy consumption during mass printing of parts. The article aims at improving quality and reducing energy consumption during 3D printing in serial production conditions. The technique’s novelty consists of a complex of production optimizations combined into a production rack to improve 3D printing. During the research, negative factors affecting print quality and their elimination were analyzed. An experimental setup for 9 printers was created. As a result, ways to increase energy efficiency according to environmental standards were implemented under the mass production of 3D parts. Overall, the applied technology allowed for reducing the time for the development of new prototypes. This made it possible to reduce the produced parts cost and allowed for implementing urgent changes in manufacturing enterprises.